Is water replenishment an effective way to improve lake water quality? Case study in Lake Ulansuhai, China - Liu, Bojun; Yang, Libin; Cui, Changyong; Wan, Weifeng; Liang, Shuntian (Frontiers in Environmental Science, 2024)
Lake water quality improvement have always been a hot topic of concern both domestically and internationally. Noncompliant outflow water quality frequently occurs, especially for lakes that rely mainly on irrigation return flow as their water source. External water replenishment to improve the water quality of lakes is gradually being recognized as a promising method, which however, is also a contro-versial method. Lake managers, in the case of constant controversy, hesitate about the appropriateness of lake water replen-ishing. Thus, taking Lake Ulansuhai in China as an example, this study aimed to construct a lake hydrodynamic and water quality model, under the constraint of multiple boundary conditions, that has sufficient simulation accuracy, and to simulate and analyze the changes in COD and TN concentrations in the lake area before and after water replenishment, and explore whether water replenishment was an effective method for improving lake water quality. The results showed that when the roughness value of Lake Ulansuhai was 0.02, the TN degradation coefficient K was 0.005/d, and the COD degradation coefficient K was 0.01/d; the simulation and measured values had the best fit, and the built model is reasonable and reliable. By external water replenishment lasting 140 days in the water volume of 4.925 × 108 m³, the COD and TN concentrations in Lake Ulansuhai could be stabilized at the Class V water quality requirement, which helped improve the self-purification ability of the lake area. Water replenishment was proved to be an effective method for improving the water quality of the lake, but water replenishment is only an emer-gency measure. Lake water replenishment is more applicable to areas with abundant water resources. External source control and internal source reduction of lake pollution and protection of lake water ecology are the main ways to improve lake water quality for water-deficient areas under the rigid constraints of water resources. In the future, key technologies for reducing and controlling pollution in irrigation areas, construction of lake digital twin platforms, and active promotion of lake legis-lation work should be the main research direction for managing the lake water environment.